The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/14651858.cd014653
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training for adults undergoing maintenance dialysis

Abstract: Analysis 1.9. Comparison 1: Any exercise versus control (no exercise/placebo exercise), Outcome 9: Systolic blood pressure...... Analysis 1.10. Comparison 1: Any exercise versus control (no exercise/placebo exercise), Outcome 10: Diastolic blood pressure... Analysis 1.11. Comparison 1: Any exercise versus control (no exercise/placebo exercise), Outcome 11: Aerobic capacity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 211 publications
4
22
1
Order By: Relevance
“…Given that the minimal clinically important difference for the 6MWT in similar patients is between 14.0 and 30.5 m [37, 38], we estimated the effect size to be moderate to large, with a moderate level of confidence in the evidence. The findings partially align with a published Cochrane meta-analysis [39], which indicated that the pooled effect of all exercise types on the 6MWT was an improvement of 49.91 m for the same population. However, our NMA offers additional insights by ranking different exercise types [13, 28, 39], showing that IAE combined with BFR is likely the most effective intervention for improving the 6MWT.…”
Section: Discussionsupporting
confidence: 87%
“…Given that the minimal clinically important difference for the 6MWT in similar patients is between 14.0 and 30.5 m [37, 38], we estimated the effect size to be moderate to large, with a moderate level of confidence in the evidence. The findings partially align with a published Cochrane meta-analysis [39], which indicated that the pooled effect of all exercise types on the 6MWT was an improvement of 49.91 m for the same population. However, our NMA offers additional insights by ranking different exercise types [13, 28, 39], showing that IAE combined with BFR is likely the most effective intervention for improving the 6MWT.…”
Section: Discussionsupporting
confidence: 87%
“…This study showed that exercise and social support are significant factors that reduce depressive symptoms and should be considered in the care of patients undergoing HD. Regular exercise or habitual physical activity is a fundamental part of living [34][35][36][37]. HCPs, particularly team members of rehabilitation, should help patients discover a suitable mode of exercise and provide guidance for home exercise.…”
Section: Limitations and Future Directionmentioning
confidence: 99%
“…Intradialytic aerobic exercise improves physical function and health-related quality of life and may ameliorate several dialysis-related symptoms. 1 , 2 , 3 , 4 , 5 , 6 , 7 Studies have demonstrated decreased cardiac stunning and improved cardiac structure and function with intradialytic aerobic exercise. 8 , 9 , 10 , 11 , 12 Findings from multiple interventional studies do not support an increased risk of IDH with intradialytic exercise because of postexercise reductions in BP.…”
mentioning
confidence: 99%